Continuance in online participation following the compromise of older adults' identity information: a literature review. (2nd November 2018) - Watson, Judy M.; Salmon, Paul M.; Lacey, David; Kerr, Don
ABSTRACT: This paper presents findings from a literature review on older adults continued use of the Internet following an identity theft incident. Globally, identity theft is increasing, statistics show that the number of older adults falling victim to identity theft is growing. Victims of identity theft suffer emotional, physical, psychological, and social problems; many change their behaviour as a result. The aim of the review was to examine literature to determine what is known regarding how older adults use the Internet and/or modify their online behaviour following an identity theft event. It was found that knowledge is lacking regarding the impact that identity theft events have on older adults' continuation of Internet use. Little research has been undertaken to understand the factors and interrelationships that contribute to the situation. The review highlights that a systems ergonomics approach should be considered as an appropriate framework to drive future research in this area.